PROTECTING CHILDREN’S HEALTH: THE ROLE OF IMMUNIZATION IN REDUCING MORBIDITY IN INDONESIA - Ahmad Syahrul Fauzi; Luthfi Ibnu Tsani; Karsinah; Feni Robingatun Khasanah (ASIAN PUBLISHER, 2025)
This study aims to analyze the effect of complete immunization on child morbidity, measured based on the child's illness history within the past month. The data used are secondary data from the Indonesia Family Life Survey (IFLS) Wave 5 conducted in 2014, with a total of 739 child respondents. The analytical method employed in this study is the probit estimation model to identify the relationship between immunization status and the likelihood of a child falling ill. The estimation results indicate that children who received complete immunization have a 50.8% lower probability of experiencing illness requiring rest compared to those who did not receive full immunization. These findings support the preventive health approach, wherein immunization plays a vital role in reducing the risk of morbidity among children. In addition, the study also finds that the higher the mother's level of education, the lower the likelihood of child morbidity. This finding underscores the importance of maternal education in health-related decision-making and better child care practices at the household level.